Selecting Tropical and Subtropical Tree Species for Wind Resistance - Mary L. Duryea; Eliana Kampf (EDIS)
FOR-120, a 13-page full color fact sheet by Mary L. Duryea and Eliana Kampf, is part of the Urban Forest Hurricane Recovery Program series. It presents the research and methodology that lead to lists of relative wind resistance for tropical and subtropical tree species. Includes recommendations for selecting and establishing tropical and subtropical species for a healthier and more wind-resistant urban forest. Published by the UF School of Forest Resources and Conservation, September 2007.